KAITAN HUKUM ISLAM DENGAN PERKEMBANGAN ILMU PENGETAHUAN DAN TEKNOLOGI - U., M. Sabir (Hunafa: Jurnal Studia Islamika, 2007)
During the prophetâs life, all legal problemsÂ  would be returned to him. Then, he wouldÂ  make a decisionÂ  on those problems. It is different from Â our contemporary era since the prophet has passed awayÂ  while there areÂ  some problems brought about by the development of science and of technology. For example, Â transplantation and insemination, both of which should be discussed by Muslim scholars to determineÂ Â  whether or not both are permitted by Islam. IfÂ  both are banned or are permitted, then whatÂ  are the conditions for banningÂ  orÂ  permitting them. Within this context, this article elaborates the relationship between Islamic law and the development of science and of technology.Kata Kunci : hukum Islam, ilmu pengetahuan, teknologi